An alternative approach of dual response surface optimization based on penalty function method - Baba, Ishaq; Midi, Habshah; Rana, Sohel; Ibragimov, Gafurjan (Hindawi Publishing Corporation, 2015)
The dual response surface for simultaneously optimizing the mean and variance models as separate functions suffers some deficiencies in handling the trade offs between bias and variance components of mean squared error (MSE). In this paper, the accuracy of the predicted response is given a serious attention in the determination of the optimum setting conditions. We consider four different objective functions for the dual response surface optimization approach. The essence of the proposed method is to reduce the influence of variance of the predicted response by minimizing the variability relative to the quality characteristics of interest and at the same time achieving the specific target output. The basic idea is to convert the constraint optimization function into an unconstraint problem by adding the constraint to the original objective function. Numerical examples and simulations study are carried out to compare performance of the proposed method with some existing procedures. Numerical results show that the performance of the proposed method is encouraging and has exhibited clear improvement over the existing approaches.